Southern African HIV Clinicians Society Guideline for the clinical management of syphilis - Remco P.H. Peters; Jeremy S. Nel; Eitzaz Sadiq; Tendesayi Kufa; Derrick P. Smit; Gillian Sorour; Nigel Garrett; Katherine Gill; Lehlohonolo Makhakhe; Nomathemba C. Chandiwana; Neil F. Moran; Karen Cohen; et al. (AOSIS, 2024)
Syphilis, 'the great imitator', caused by Treponema pallidum infection, remains a complex and multifaceted disease with a rich history of clinical diversity. This guideline aims to be a comprehensive guide for healthcare workers in Southern Africa, offering practical insights into the epidemiology, pathogenesis, clinical manifestations, diagnostic testing, therapeutic principles, and public health responses to syphilis. Although the syphilis burden has declined over the years, recent data indicate a troubling resurgence, particularly among pregnant women and neonates. This guideline highlights the diagnostic challenges posed by syphilis, stemming from the absence of a single high-sensitivity and -specificity test. While treatment with penicillin remains the cornerstone of treatment, alternative regimens may be used for specific scenarios. We highlight the importance of thorough patient follow-up and management of sex partners to ensure optimal care of syphilis cases. In the context of public health, we emphasise the need for concerted efforts to combat the increasing burden of syphilis, especially within high-risk populations, including people living with HIV.